Contrasting community assembly processes structure lotic bacteria metacommunities along the river continuum. (10th December 2020) - Gweon, Hyun S.; Bowes, Michael J.; Moorhouse, Heather L.; Oliver, Anna E.; Bailey, Mark J.; Acreman, Michael C.; Read, Daniel S.
Summary: The heterogeneous nature of lotic habitats plays an important role in the complex ecological and evolutionary processes that structure the microbial communities within them. Due to such complexity, our understanding of lotic microbial ecology still lacks conceptual frameworks for the ecological processes that shape these communities. We explored how bacterial community composition and underlying ecological assembly processes differ between lotic habitats by examining community composition and inferring community assembly processes across four major habitat types (free‐living, particle‐associated, biofilm on benthic stones and rocks, and sediment). This was conducted at 12 river sites from headwater streams to the main river in the River Thames, UK. Our results indicate that there are distinct differences in the bacterial communities between four major habitat types, with contrasting ecological processes shaping their community assembly processes. While the mobile free‐living and particle‐associated communities were consistently less diverse than the fixed sediment and biofilm communities, the latter two communities displayed higher homogeneity across the sampling sites. This indicates that the relative influence of deterministic environmental filtering is elevated in sediment and biofilm communities compared with free‐living and particle‐associated communities, where stochastic processes play a larger role.